Teori Konvergensi Simbolis (Symbolic Convergence Theory) Dalam Kajian Pustaka - Dorien Kartikawangi (Jurnal InterAct, 2013)
This literature study looks into details about the application of Symbolic Convergence Theory (SCT). The theory was introduced by Bormann within a constructivist paradigm which successfully went through debate and argumentation from diverse standpoints. This piece of theoretical analysis suggests that SCT may be applied as an analytical tool in the constantly changing environment driven by the globalization and the significant role of information communication technology today. The argument hereby are presented systematically from the heuristic value of SCT, history, anatomic element, uses in problem solving, explanation of SCT critics, and its role for the future research.